Physical drivers of the summer 2019 North Pacific marine heatwave - Dillon J. Amaya (Nature Portfolio, 2020)
Marine heatwaves are threatening ocean ecosystems with increasing frequency, but their seasonal drivers are unknown. Here, the authors determine that summertime blobs of warm temperature anomalies in the Pacific occur as a result of prolonged weakening in the North Pacific High-Pressure System.